EX-CORPORATION: ON MALE BIRTH FANTASIES - Kanz, Christine (Imaginations: Journal of Cross-Cultural Image Studies, 2011)
Between 1890 and 1933, male birth fantasies became a widespread phenomenon in European culture. One of the key examples of male birth fantasies is Filippo Tommaso Marinetti’s “African” novel Mafarka the Futurist. The novel’s protagonist, Mafarka, gives birth to a child by his will power and by drawing on diverse formations of knowledge, from alchemy to theories of evolution. In addition to the consideration given the psycho-historical, cultural, and scientific contexts of male birth fantasies in the avant-garde, the contribution reflects on sibling encryptment within the relationship to the mother as one more aspect of a span of genealogy one might term “Maternal Modernity.” Christine Kanz is Professor of German Literature at Ghent University in Belgium. Her contribution refers to her 2009 book Maternale Moderne. Männliche Gebärphantasien zwischen Kultur und Wissenschaft, 1890- 1933. In addition she edited several collections and authored another book on Ingeborg Bachmann, and numerous articles and reviews in the area of interdisciplinary studies. Before entering the Academy of Fine Arts Karlsruhe, class of Daniel Roth, in 2008, Adam Cmiel trained in various media in Bad Dürkheim, Hamburg, Mannheim, and Trier. He has participated in nine exhibitions since the onset of his studies in Karlsruhe.